2022
DOI: 10.3390/tropicalmed7100312
|View full text |Cite
|
Sign up to set email alerts
|

Space–Time Clustering and Socioeconomic Factors Associated with Mortality from Diarrhea in Alagoas, Northeastern Brazil: A 20-Year Population-Based Study

Abstract: Acute diarrhea is the second leading cause of death among children in developing countries and is strongly related with the socioeconomic conditions of the population. In Brazil, data show a drop in the diarrhea mortality rate. Nevertheless, the northeastern region still has the most deaths. Considering this, we analyze high-risk areas for diarrhea- and gastroenteritis-related deaths, and their association with social determinants of health (SDH) in the state with one of the worst human development indicators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(43 reference statements)
0
0
0
Order By: Relevance
“…For this reason, the better conditions for preventing diarrhea reflected by the higher HDIs have probably contributed to low-risk clusters of hospitalization for the disease. This contrasts with the setting identified in Alagoas state (which has the worst HDI) 39 for mortality rates of diarrhea for both age groups from 2011 to 2020 ( ).…”
Section: Discussioncontrasting
confidence: 62%
“…For this reason, the better conditions for preventing diarrhea reflected by the higher HDIs have probably contributed to low-risk clusters of hospitalization for the disease. This contrasts with the setting identified in Alagoas state (which has the worst HDI) 39 for mortality rates of diarrhea for both age groups from 2011 to 2020 ( ).…”
Section: Discussioncontrasting
confidence: 62%
“…Socioeconomic status was one of the main causes of diarrheal diseases among children in China (15). A study also found that the diarrheal diseases are still a crucial public health, especially in the poorest areas (16,17). Poorly populated areas generally have poor waste disposal systems, unclean drinking water sources, and difficulty accessing health services, thereby increasing the incidence of diarrhea and gastrointestinal infections (16).…”
Section: Discussionmentioning
confidence: 99%